The experience of nurse anaesthetists in assessing postoperative pain in orthopaedic patients - Ferid Krupić; Kemal Grbić; Mirza Bišćević; Mahir Jašarević; Svemir Čustović; Sebastian S. Mukka (Medicinski glasnik, 2019)
Aim: To explore the experiences of anaesthesia nurses in assessing postoperative pain in patients undergoing total hip and/or knee arthroplasty. Methods: Data were collected through four focus group interviews (FGI) using the critical incident technique (CIT). The participants were six men and 12 women, all registered nurses with further education in anaesthesia with at least five-year experience of caring for patients on a postoperative ward. Results: Maintaining communication with orthopaedic patients, different ways to assess pain, the assessment of unresponsive patients, using pain assessment scales and different work circumstances influencing their use, were stated as the main problems the nurses emphasize while assessing the pain of patients. Conclusion: Skills related to observing the behaviour and experience of pain in different individuals are needed to ensure an understanding of patients' pain, as well as the patients' ability to estimate their pain, where the intensity of the pain varies in different patients. Further studies are needed to examine the way health professionals assess pain, depending on the patients' ability to transform their pain from a subjective feeling into an objective numeric grade. The way individuals assess their pain differently and the way the resulting knowledge and experience of postoperative care may help nurses and other health-care professionals.
Keywords: experiences; nurse anaesthetists; orthopaedics; pain; qualitative research